2013
DOI: 10.1007/s10899-013-9367-8
|View full text |Cite
|
Sign up to set email alerts
|

Disordered gambling and co-morbidity of psychiatric disorders among college students: An examination of problem drinking, anxiety and depression

Abstract: We assessed the occurrence of co-morbid psychiatric disorders (i.e., problem drinking, anxiety, and depression) among college students who met the threshold for disordered gambling. The participants included a large sample of undergraduate students (n = 1,430) who were enrolled in an introductory health course at a large, southeastern university in Spring 2011 and completed an online assessment that included scales to assess disordered gambling, problem drinking, anxiety, and depression. We calculated screenin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
44
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(53 citation statements)
references
References 33 publications
6
44
0
1
Order By: Relevance
“…In addition to examining common risk factors for problematic gambling and gaming, it is of interest to examine the comorbidity between gambling-and gaming-related behaviours and mental health disorders, such as depression. There is ample research indicating significant correlations between gambling, problem gambling, and depression (Bonnaire, Bungener, & Varescon, 2009;Gupta & Derevensky, 1998a;Kim, Grant, Eckert, Faris, & Hartman, 2006;Martin, Usdan, Cremeens, & Vail-Smith, 2014;McCormick, Russo, Ramirez, & Taber, 1984;Potenza et al, 2001). Adolescents with gambling problems report higher rates of depression, alcohol abuse, anxiety, and are at heightened risk for both reported suicide ideation and attempts (Desai, Maciejewski, Pantalon, & Potenza, 2005;Kaminer, Burleson, & Jadamec, 2002;Molde, Pallesen, Bartone, Hystad, & Johnsen, 2009;Moodie & Finnigan, 2006a; While in its infancy, the research on gaming and depression supports a positive relationship between problematic gaming (as measured by time spent playing or the Game Addiction Scale (Lemmens et al, 2011)), and depression (Desai, Krishnan-Sarin, Cavallo, Gambling and Video Game Playing 26 & Potenza, 2010;Lemmens et al, 2011;Mentzoni et al, 2011;Messias, Castro, Saini, Usman, & Peeples, 2011).…”
Section: Gendermentioning
confidence: 99%
“…In addition to examining common risk factors for problematic gambling and gaming, it is of interest to examine the comorbidity between gambling-and gaming-related behaviours and mental health disorders, such as depression. There is ample research indicating significant correlations between gambling, problem gambling, and depression (Bonnaire, Bungener, & Varescon, 2009;Gupta & Derevensky, 1998a;Kim, Grant, Eckert, Faris, & Hartman, 2006;Martin, Usdan, Cremeens, & Vail-Smith, 2014;McCormick, Russo, Ramirez, & Taber, 1984;Potenza et al, 2001). Adolescents with gambling problems report higher rates of depression, alcohol abuse, anxiety, and are at heightened risk for both reported suicide ideation and attempts (Desai, Maciejewski, Pantalon, & Potenza, 2005;Kaminer, Burleson, & Jadamec, 2002;Molde, Pallesen, Bartone, Hystad, & Johnsen, 2009;Moodie & Finnigan, 2006a; While in its infancy, the research on gaming and depression supports a positive relationship between problematic gaming (as measured by time spent playing or the Game Addiction Scale (Lemmens et al, 2011)), and depression (Desai, Krishnan-Sarin, Cavallo, Gambling and Video Game Playing 26 & Potenza, 2010;Lemmens et al, 2011;Mentzoni et al, 2011;Messias, Castro, Saini, Usman, & Peeples, 2011).…”
Section: Gendermentioning
confidence: 99%
“…Several cross-sectional studies have focused on the overlap between gambling and substance use among college students and have consistently observed significant positive associations between gambling, problem gambling, and alcohol use (Bhullar et al, 2012b; Engwall et al, 2004; Goudriaan et al, 2009; Huang et al, 2011; LaBrie et al, 2003; Martens et al, 2009; Martin et al, 2014; Stuhldreher et al, 2007; Vitaro et al, 2001). For example, Bhullar et al (2012b) found that, compared with students who did not meet criteria for binge drinking, binge drinking college students were more likely to participate in poker, Internet gambling, sports betting, and office pools.…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis by Lorains, Cowlishaw and Thomas (2011) indicated among those who exhibit subthreshold or probable pathological gambling disorder, 57.5% reported any substance use disorder, 37.9% reported any mood disorder, and 37.4% reported any anxiety disorder in their lifetime. Specifically among college students, disordered or more frequent gambling is positively associated with higher levels and problematic patterns of alcohol and other drug use (Bhullar, Simons, Joshi, & Amoroso, 2012; Engwall, Hunter & Steinberg, 2004; Martens et al, 2009; Martin, Usdan, Cremeens, & Vail-Smith, 2014), including stimulants such as amphetamines (LaBrie, Shaffer, LaPlante, & Wechsler, 2003; Lee, Ghandour, Takache, & Martins, 2014). …”
mentioning
confidence: 99%